Analisis Strategi Linguistik Richard Eliezer: Penggunaan Frasa "Tidak Tahu" dan "Saya Rasa" di Pengadilan. - Saud, Jefriyanto; Anwar, Miftahulkhairah; Prihantoro, Prihantoro (Jurnal Ilmiah Global Education, 2024)
Language serves as a strategic tool for managing legal and emotional pressures during trials. This study focuses on the use of the phrases "tidak tahu" and "saya rasa" in Richard Eliezer's testimony in the Brigadier J case, reflecting defensive communication strategies. The issues examined are how these phrases are used to evade legal responsibility and how emotional pressure influences speech patterns. Using a descriptive quantitative and qualitative approach, the results indicate that the phrase “tidak tahu" (used 41 times) is employed to avoid accountability, while "saya rasa" (used 4 times) reflects subjective opinions aimed at risk mitigation. These findings reveal a close relationship between the emotional pressure experienced by the witness and their language choices, as well as the importance of linguistic analysis in understanding legal communication.